2022
DOI: 10.1021/acssuschemeng.2c02830
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Engineering of Metal–Organic Framework-Derived Trimetallic NiCoFe-Layered Double Hydroxides as Efficient Electrocatalysts for Water Oxidation Reaction

Abstract: The development of active, noble-metal-free electrocatalysts for the oxygen evolution reaction (OER) with low cost and high earth abundance for energy-efficient electrolysis applications has been a challenging task. In this study, a two-step chemical process that involves co-precipitation followed by alkaline treatment is proposed to fabricate trimetallic NiCoFe-layered double hydroxide (t-NiCoFe-LDH) materials for OER using trimesic acid as a metal−organic framework (MOF) ligand. Owing to the unique aloe-vera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…45 The energy gap of 14.1 eV between Co 2p 1/2 and Co2p 3/2 indicates the formation of the Co(OH) 2 phase, while the Co 3+ are ascribed to CoOOH species. 46,47 Moreover, the peaks at 786.8 eV and 801.6 eV are attributed to satellite features 2p 3/2 and 2p 1/2 , respectively. In the C 1s spectrum (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…45 The energy gap of 14.1 eV between Co 2p 1/2 and Co2p 3/2 indicates the formation of the Co(OH) 2 phase, while the Co 3+ are ascribed to CoOOH species. 46,47 Moreover, the peaks at 786.8 eV and 801.6 eV are attributed to satellite features 2p 3/2 and 2p 1/2 , respectively. In the C 1s spectrum (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…35 The inclusion of multi-metallic elements in catalysts boosts the availability of additional electrons from adjacent atoms while also increasing the number of active sites. [38][39][40][41][42][43] Li et al suggested that more exposed and accessible active sites in trimetallic MILs (MIL stands for Materials of Institute Lavoisier) result from multi-metallic centers, which demonstrated improved OER activity. 40 Niu et al created a hierarchical Ni-Co-Fe hydr(oxy)oxide@NiCo LDH yolkshelled structures beginning from MIL-88A as an effective OER electrocatalyst, and beneting from the structural advantages and synergistic effects of the Ni, Co, and Fe elements.…”
Section: Introductionmentioning
confidence: 99%
“…Lou et al 9 prepared NiFe LDH with interconnected ultrathin layers (with a very low overpotential equal to 280 mV at 10 mA cm −2 ) using a self-templated method. Kim et al 10 prepared a metal–organic framework derived NiCoFe LDH using a two-step process (co-precipitation and alkaline treatment). The resulting composite was very stable and exhibited an overpotential of 277 mV at 10 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%